2016
DOI: 10.1353/hpu.2016.0023
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Health Assets of Somali and Oromo Refugees and Immigrants in Minnesota: Findings from a Community-Based Participatory Research Project

Abstract: This community-based participatory research study sought to identify the cultural health assets of the Somali and Oromo communities in one Minnesota neighborhood that could be mobilized to develop culturally appropriate health interventions. Community asset mappers conducted 76 interviews with Somali and Oromo refugees in in Minnesota regarding the cultural assets of their community. A community-university data analysis team coded data for major themes. Key cultural health assets of the Somali and Oromo refuge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 20 publications
1
21
0
8
Order By: Relevance
“…The African countries where most participants originated from, were Eritrea and Somalia. There is little research on Eritrean oral health, but several studies emphasize the importance of oral hygiene in Somalian culture and religion [13][14][15]. Moreover, traditional Somalian diet is low in fat and sugar, which may contribute to the lower caries prevalence in the African participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The African countries where most participants originated from, were Eritrea and Somalia. There is little research on Eritrean oral health, but several studies emphasize the importance of oral hygiene in Somalian culture and religion [13][14][15]. Moreover, traditional Somalian diet is low in fat and sugar, which may contribute to the lower caries prevalence in the African participants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, traditional Somalian diet is low in fat and sugar, which may contribute to the lower caries prevalence in the African participants. But research has demonstrated a tendency of Somali refugees to easily adapt to a Western diet [13,14]. Therefore, dietary information to encourage continuation of positive cultural traditions may be important to emphasize in future reception programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO 'healthy settings' initiative is an example of this approach, where, according to the 1986 Ottawa Charter for Health Promotion, 'Health is created and lived by people within the settings of their everyday life; where they learn, work, play, and love' (WHO no date). Work on this has been carried out within schools, workplaces, hospitals, prisons and universities (Dooris 2005;, but virtually no attention has been paid to places of worship as 'healthy settings', with the exception of Corcoran et al (2013) approach looks for things that already exist within a community that are being or could be leveraged by that community to achieve their goals (Foot and Hopkins 2010;Lightfoot et al 2016).…”
Section: Pws As Therapeutic Placesmentioning
confidence: 99%
“…Knowledge, awareness, specific religious or cultural factors, embarrassment or modesty, fear, language barriers, inconvenient clinic hours, and childcare needs have been identified as barriers for Somali women in both the United States and London, United Kingdom (Abdullahi et al, 2009;Carroll et al, 2007). Studies in the Minneapolis-St. Paul metropolitan area have also identified that East African refugees learn about health information at social gatherings and are more likely to trust health information that has been shared and vouched for by trusted East African peers (Lightfoot, Blevins, Lum, & Dube, 2016;Simmelink, Lightfoot, Dube, Blevins, & Lum, 2013).…”
mentioning
confidence: 99%